Improvement of Micro UAV Performance using Tandem-Wing Design - Khudair, Omar Abdulrazzak; Aziz, Shurouq Adnan; Munshid, Huda Ali; Rzokhy, Haedar Muhey; Fared, Samiah (Nahrain University College of Engineering Journal, 2017)
The main objective for the present work is related with design of MAV to get high performance and long endurance used for surveillance and monitoring in military and civilian. The most important problem that faced the MAV is flying with low Reynolds numbers (Mach number is too law) and high lift with avoid high drag, the tandem-wing design is sucseceful and more reliable for this purpose because it reduced the drag to a half and gives good aerodynamic chractrastices when it?s compared with the conventional wing design.The dimensions of a MAV are 120mm length, wing span 130mm ( from tip to tip) and 12g in weight (the standard weight of MAV about 5- 20 g) with rang 50m (is the distance that the aircraft cut from point to another).The softwares that used in the present work are (Java foil, Soled works, ANSYS, J2) to prove the results.For the aerodynamic coefficients (CL, CD) were checked for two models (Tandem wing and conventional wing) by using ANSYS. To ensure that the design is successful we made aSimulation for the design by using (The J2 Universal Tool-Kit for Aircraft Dynamics) software and used to testing the aerodynamic characteristic and performers, stability and control. The major benefits of the tandem wings are to reduce drag to half and increase the lift rather than conventional wing by separating the two wings. Java foil was used to calculate the aerodynamics coefficients for the airfoil.